PENGARUH ECONOMIC VALUE ADDED (EVA) DAN RETURN ON ASSET (ROA) TERHADAP MARKET VALUE ADDED (MVA) - SUTOMO MANDALA PUTRA; ZAINAL ILMI; IRSAN TRICAHYADINATA (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
The Influence of Economic Value Added (EVA) and Return on Assets (ROA) of Market Value Added (MVA). The research study automotive sub-sector in the Indonesia Stock Exchange (BEI). (Under the guidance of Dr. ZAINAL LLMI, SE., MBA and Dr. Irsan Tricahyadinata, SE., MSi). The purpose of research is to analyze the influence of Economic Value Added (EVA) and Return on Assets (ROA) of Market Value Added (MVA) (Study research sub automotive sector in the Indonesia Stock Exchange (BEI). The sample used in this study are 7 sub company of the automotive sector using criteria through purposive sampling method. Analysis of the data used in this study is the classical assumption test and multiple linear regression using SPSS 20. the results of this study indicate that the Economic Value Added (EVA) has no effect on the Market Value Added (MVA). Return on Asset (ROA) significantly affects the Market Value Added (MVA).Keywords: Economic Value Added, Return on Asset and Market Value Added.